2002
DOI: 10.1097/00005373-200204000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Hsp 72 Measured Early after Trauma Correlate with Survival

Abstract: Hsp 72 can be detected in the serum of severely traumatized patients within 30 minutes after injury. Elevated initial serum levels of Hsp 72 (serum levels > 15 ng/mL) are associated with survival after severe trauma, but are not related to the incidence or severity of the postinjury inflammatory response or organ dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
109
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 25 publications
9
109
1
2
Order By: Relevance
“…Second, could it be possible that extracellular Hsp70 serves an as yet undefined cytoprotective function at lower levels as a normal response to infection or stress, and once a certain critical threshold is attained potentiate the dysregulated inflammatory response that subsequently results in significant auto-injury to the host? The results correlating increased Hsp70 levels to improved outcome in adults with trauma support this latter concept (141). Future investigation in this area will likely address these questions.…”
Section: Stress Proteins and Innate Immunitymentioning
confidence: 71%
See 2 more Smart Citations
“…Second, could it be possible that extracellular Hsp70 serves an as yet undefined cytoprotective function at lower levels as a normal response to infection or stress, and once a certain critical threshold is attained potentiate the dysregulated inflammatory response that subsequently results in significant auto-injury to the host? The results correlating increased Hsp70 levels to improved outcome in adults with trauma support this latter concept (141). Future investigation in this area will likely address these questions.…”
Section: Stress Proteins and Innate Immunitymentioning
confidence: 71%
“…Hsp70 is the most highly induced stress protein in cells and tissues undergoing the stress response (3), and is known to be induced in patients with a variety of critical illnesses or injuries (140)(141)(142)(143). Microinjection of anti-Hsp70 antibody into cells impairs their ability to achieve thermotolerance (144), and increased expression of Hsp70 by gene transfer/transfection has been demonstrated to confer protection against in vitro toxicity secondary to lethal hyperthermia (145), endotoxin (8), nitric oxide (9), hyperoxia (130), and in vivo ischemia-reperfusion injury (146)(147)(148).…”
Section: Stress Proteins and Cytoprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recognised that Hsp70 are present in the peripheral circulation of healthy individuals (Pockley et al 1998;Dhingra et al 2006), and their levels increase after intensive exercise (Febbraio et al 2002;Fehrenbach et al 2005). Elevation of serum Hsp70 was reported in patients with soft tissue trauma (Pittet et al 2002;Flohe et al 2007), with peripheral and renal vascular disease (Wright et al 2000), after acute myocardial infarction (AMI; Dybdahl et al 2005;Satoh et al 2006), or coronary artery bypass grafting (Dybdahl et al 2002), preeclampsia (Molvarec et al 2006) and haemolytic anemia elevated liver enzymes low platelet count (HELLP) syndrome (Molvarec et al 2007). Genth-Zotz et al (2004) found elevated serum Hsp70 levels in CHF patients and a correlation between the Hsp70 and disease severity and cachexia, but not with survival.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, Hsp70 may be induced by a series of pathological stimuli including ischemia, exitotoxicity and inflammatory responses. (73) Pittet et al (74) showed that the Hsp72 (member of the Hsp70 family) can be detected in the serum of patients with severe trauma within 30 minutes after trauma and that high levels are associated with favorable outcome after trauma. Recently we investigated the role of the Hsp70 protein as a predictive marker of mortality for severe TBI in men.…”
Section: Cellular Stress Proteinsmentioning
confidence: 99%